The Effect of Work Ethics on Job Performance in International SMEs in Al-Hassan Industrial Estate - Bataineh, Mohammad T. (International Review of Management and Marketing, 2020)
The purpose of this study is to explore how work ethics (through work ethics elements: integrity, responsibility, equality and self-discipline) effects on employee's job performance in SMEs in Al-Hassan Industrial Estate. A survey was conducted on 257 employees in SMEs in Al-Hassan Industrial Estate. Hierarchical regression was used to model the effect of work ethics on employee's job performance. The work ethics elements are integrity, responsibility, equality and self-discipline. The results show that work ethics is improved employee's job performance in SMEs in Al-Hassan Industrial Estate. Moreover, the elements of work ethics (integrity, responsibility, equality and self-discipline) also improved employee's job performance. Moreoverthe company should be provided the necessary information to all auditors frankly, the managers should be authorized responsibility to employees, managers should be treated all employees fairly, and the workers should be carried out the tasks assigned to them by self-monitoring. Keywords: Small and medium-sized enterprises, work ethics, job performance, integrity, responsibility, equality and self-discipline. JEL Classifications: L2, L32 DOI: https://doi.org/10.32479/irmm.10364